Enhancing Financial Technology Operations: A Comprehensive Evaluation Using COBIT 2019 Framework - Sherly, Sherly; Fianty, Melissa Indah (Jurnal Riset Informatika, 2024)
This research aims to enhance information technology (IT) governance in a financial technology company by focusing on peer-to-peer lending services. The main challenges faced by the company involve a lack of system design details, leading to post-implementation imperfections and negative impacts on business process performance, including unnecessary delays and adjustments. The lack of transparency in system evaluation is also a hindrance caused by incomplete recording of test results. Therefore, this research aims to address these challenges by utilizing the COBIT 2019 framework. The study employs a qualitative approach, utilizing data obtained through interviews and literature studies supported by the COBIT Tool Kit. The analysis is conducted on three main objectives: security management, solution identification, and IT change management, to identify disparities between the current status and desired targets. The analysis results highlight the need for improvements in specific aspects, including the lack of system design details, more precise information in the change process, and deficiencies in recording test results. Recommendations for improvement involve the development of more detailed guidelines for system design, enhanced documentation of changes, and improvements in testing instructions and result reporting. Additionally, recommendations focus on enhancing capabilities through proactive evaluation, refining security plans, developing more adaptive solution acquisition strategies, and improving testing practices. Thus, this research underscores the importance of strategic improvements within the IT and Information Systems governance framework to shape a more effective and transparent operational environment in Financial Technology companies.